Université, administration publique et culture juridique. Considérations à propos de l’institution des Facultés de sciences politiques en Italie - Paolo Alvazzi del Frate (Cahiers Jean Moulin)
At the end of the 19th century, there was a strong demand in Italy for providing to public officials a training that would not be exclusively legal. In 1924, political studies were separated from the legal education with the creation at the University of Rome of a School (then Faculty) of Political Science, considered as the training school of the administrative and diplomatic elite. After the fall of the Fascist Regime, the Faculty of Political Science experienced a period of profound crisis and, despite a series of reforms in the 1960s and 1970s, did not play a major role in training civil servants. This training therefore remained in the law schools where the teachings are dogmatic and primarily intended for future lawyers and judges. This reinforced the rigid, static and mainly formalistic culture of the Italian public administration.